Bibliometrics and characterization of the undergraduate theses of the Faculty of Veterinary Medicine and Zootechnics of Universidad Nacional Micaela Bastidas de Apurímac, Peru - Contreras, Walter (2020)
The aim of this study was to quantify and characterize the undergraduate theses of the Faculty of Veterinary Medicine and Zootechnics (FMVZ) of the Universidad Nacional Micaela Bastidas de Apurímac (UNAMBA), Peru. All of the theses defended in the period 2012-2018 were reviewed. A survey was carried out among the thesis supervisors regarding the publications derived from the theses. Descriptive statistics were used to determine the frequencies and proportions. Besides, multiple correspondence analysis to estimate relationships between the variables and their categories were conducted. Of the 79 registered theses, the highest number of dissertations were done in 2018 (29.1%), the two main areas of research were animal production (54.4%) and public health (24%), the highest number was done on bovines (21.5 %), alpacas (16.5%) and dogs (16.5%), and 72.2% of the theses correspond to observational research. Furthermore, 4/20 supervisors concentrated 50% of the theses, 13/20 lecturers presented the highest appointments as thesis jurors, and 20.2% of the thesis results were published in indexed journals. The variables species and advisor had a stronger relationship with each other than the variables area of advice and type of research.